Peculiarities of consolidation of criminal penalties and the justice of the final sentence in the practice of Lithuanian courts - Pranka, Darius (Kriminologijos studijos, 2024)
Scholars of criminal law have not considered the issue of consolidation of criminal penalties for some time, and it has been undeservedly forgotten. However, the method of consolidation of criminal penalties and the size of the final punishment are very important for the defendant. In addition, in judicial practice, there are often various problems related to the correct and appropriate summation of sentences. It is sometimes very easy to get lost in the labyrinths of sentence sizes, numbers and calculation of the last sentence. The article begins by presenting a negative example of judicial practice, when the lower court, ignoring the decision of the appeal court, decides to postpone the execution of the prison sentence after the sentence has been combined. Next, the author raises the question of why criminal law provides only the minimum amount of penalties to be added. Still, when putting together several sentences, adding at least the minimum part of the penalties is not mandatory. On the other hand, in the context of this problem, we can reasonably doubt whether, in cases where the offender commits several dozen or several hundred criminal acts, putting together the punishments and adding a minimum part of each punishment, the last punishment is not too severe. Finally, at the end of the article, the difficulties of putting together punishments are shown when punishments have to be shared by simultaneous application of Article 63 of the Criminal Code and Article 64 of the Criminal Code.